Examining the potential for resource‐dependent female reproductive fluid‐sperm interactive effects in a livebearing fish. (9th March 2023) - Fernlund Isaksson, Erika; Fitzpatrick, John L.
Abstract: Sexually selected traits can be costly to produce and maintain. The amount of resources available to an individual is therefore expected to influence investment in costly sexual traits. While resource‐dependent expression of sexually selected traits has traditionally been examined in males, resource limitation can also influence how sexual selection operates in females. Female reproductive fluids are thought to be costly to produce and may play an important role in shaping the outcome of postcopulatory sexual selection by influencing sperm performance. However, we know surprisingly little about whether and how female reproductive fluids are influenced by resource limitation. Here, we examine if resource restriction influences female reproductive fluid‐sperm interactive effects in the pygmy halfbeak ( Dermogenys collettei ), a small internally fertilizing freshwater fish where females store sperm. After experimentally altering female diets (high vs. restricted diets), we compared how female reproductive fluids influence two key metrics of sperm quality: sperm viability and velocity. While female reproductive fluids enhanced sperm viability and velocity, we found no evidence that female diet influenced the interactive effect between female reproductive fluids and sperm viability or velocity. Our findings build on the growing evidence that female reproductive fluids influence sperm performance and call for further attention to be devoted to understanding how resource quantity and quality influence how female reproductive fluids affect sperm performance. Abstract : Female reproductive fluids (FRF) supercharge male sperm velocity and viability in a livebearing fish. These effects were similar if females were fed a resource‐rich diet or a poor diet.